Influence of AC interference to corrosion of Q235 carbon steel. (August 2013) - Li, Y T; Li, X; Cai, G W; Yang, L H
Abstract : The alternating current (AC) has a strong influence on the corrosion of carbon steel Q235 in soil. AC corrosion 1–3 was investigated by morphology observation, weight loss analysis and electrochemical measurement. The results of morphology observation and weight loss analysis showed that AC increased the corrosion rate and the influence was weakened when a protective layer was built up. The electrochemical tests confirmed that in the presence of AC, the corrosion potential shifted toward the negative direction and the exchange current density increased. 4–9